2020
DOI: 10.1002/ijc.33028
|View full text |Cite
|
Sign up to set email alerts
|

Crypt residing bacteria and proximal colonic carcinogenesis in a mouse model of Lynch syndrome

Abstract: Colorectal cancer is a multifactorial disease involving inherited DNA mutations, environmental factors, gut inflammation and intestinal microbiota. Certain germline mutations within the DNA mismatch repair system are associated with Lynch syndrome tumors including right‐sided colorectal cancer with mucinous phenotype and presence of an inflammatory infiltrate. Such tumors are more often associated with bacterial biofilms, which may contribute to disease onset and progression. Inflammatory bowel diseases are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
4
14
0
Order By: Relevance
“…In humans, fecal samples from patients with a carcinoma are enriched in species belonging to the genus Bacteroides, Parabacteroides and Escherichia, besides others, compared to patients with adenomas and healthy controls. These bacterial taxa are also associated with inflammation and carcinogenesis in mouse model [34].…”
Section: Resultsmentioning
confidence: 99%
“…In humans, fecal samples from patients with a carcinoma are enriched in species belonging to the genus Bacteroides, Parabacteroides and Escherichia, besides others, compared to patients with adenomas and healthy controls. These bacterial taxa are also associated with inflammation and carcinogenesis in mouse model [34].…”
Section: Resultsmentioning
confidence: 99%
“…TMB refers to the total number of substitution, insertion, and deletion mutations per megabase in the exon coding region of the evaluated gene in the tumor cell genome [ 13 ]. Previous studies have shown that changes in the pathogenicity of cell functions due to changes in the genome are clinically called “driver mutations,” which can lead to tumors [ 14 ]. In this study, the level of TMB in advanced gastric cancer was 5–14, with an average of 8.58 ± 0.61.…”
Section: Discussionmentioning
confidence: 99%
“…They registered an accumulation of follicular T-helper (TFH) cells in CRC patients and mice and the suppression of IEC apoptosis. This effect could be linked to the impairment of the immunosurveillance mechanisms by chemotherapy directed against CRC in mice [ 100 ]. Protective immune responses in the ileum were associated with the colonization of specific bacteria such as Bacteroides fragilis and Erysipelotrichaceae that stimulate the production of programmed cell death (PD-1) molecules +TFH by secretion of interleukin 1R1 and interleukin 12.…”
Section: Microbiotamentioning
confidence: 99%
“…Protective immune responses in the ileum were associated with the colonization of specific bacteria such as Bacteroides fragilis and Erysipelotrichaceae that stimulate the production of programmed cell death (PD-1) molecules +TFH by secretion of interleukin 1R1 and interleukin 12. Moreover, the demonstration of apoptosis in the ileum can be considered a prognostic factor for CRC patients [ 100 ].…”
Section: Microbiotamentioning
confidence: 99%
See 1 more Smart Citation